2019 9th International Conference on Recent Advances in Space Technologies (RAST) 2019
DOI: 10.1109/rast.2019.8767431
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of Cellular Structures Using Weightlessness as a Biotechnological Tool

Abstract: Gravity is an important biomechanical signal effecting the morphology and function of organisms. Reduction of gravitational forces, as experienced during spaceflight, cause alterations in the biological systems. Magnetic levitation technique is one of the most recent ground-based technology to mimic weightlessness environment. In addition to providing a platform to investigate biological effects of the weightlessness, this platform presents a novel opportunity to biofabricate 3dimensional (3D) structures in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Also, it was shown that sickle cell disease which results in increased density of erythrocytes (Knowlton et al, 2015) and drug treatments that cause density changes in bacteria and yeast (Durmus et al, 2015) can be tested with magnetic levitation systems and portable platforms of the system enable applications for point of care testing (Stephanie Knowlton et al, 2017; Yenilmez, Knowlton, & Tasoglu, 2016; Yenilmez, Knowlton, Yu, et al, 2016). After the successful application of the magnetic levitation system to single cell‐based studies, it became a focus of interest as a biofabrication tool for tissue engineering (Anil‐Inevi, Yalcin‐Ozuysal, et al, 2019; Mishriki et al, 2019). Previously, the suitability of a long‐term cell culture in magnetic levitation platform was demonstrated by single and coculture culture of cancer and stem cells (Anil‐Inevi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was shown that sickle cell disease which results in increased density of erythrocytes (Knowlton et al, 2015) and drug treatments that cause density changes in bacteria and yeast (Durmus et al, 2015) can be tested with magnetic levitation systems and portable platforms of the system enable applications for point of care testing (Stephanie Knowlton et al, 2017; Yenilmez, Knowlton, & Tasoglu, 2016; Yenilmez, Knowlton, Yu, et al, 2016). After the successful application of the magnetic levitation system to single cell‐based studies, it became a focus of interest as a biofabrication tool for tissue engineering (Anil‐Inevi, Yalcin‐Ozuysal, et al, 2019; Mishriki et al, 2019). Previously, the suitability of a long‐term cell culture in magnetic levitation platform was demonstrated by single and coculture culture of cancer and stem cells (Anil‐Inevi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Diamagnetic levitation is another laboratory-based method to simulate microgravity on earth. While clinostats, RWV, and RPM cancel the gravity vector through rotation over the period, diamagnetic levitation counteracts the gravitational force (𝐹 𝑔 ) by levitating the object with magnetic force (𝐹 𝑚 ) [85]. The force Fm acting on an object is given as [85],…”
Section: Random Positioning Machinementioning
confidence: 99%
“…This system levitates materials in paramagnetic solutions under a low magnetic field (<0.5 T) that is generated by two rectangular permanent magnets with the same poles facing each other (Anil‐Inevi et al,2019b; Durmus et al,2015; Mirica et al,2009). However, this setup only allows biofabrication applications in microcapillaries, limiting working volumes for cells (Anil‐Inevi et al,2018,2019a; Sarigil et al,2020; Türker et al,2018). Increasing the size of living structures is of prime importance for straightforward implementation of testing protocols by providing an adequate number of cells (Menasche et al,2019; Shen et al,2017; Van Peer et al,2012), and for the production of sizable tissue engineering constructs (Morrison et al,2016; Park et al,2019).…”
Section: Introductionmentioning
confidence: 99%